Case Report: Mycobacterium abscessus knee joint infection following herbal steam bath: successful short-course oral therapy in an immunocompetent patient - Jiaqing Ye; Jiaqing Ye; Jiahao Hao; Cuiying Zheng; Minghui Song; Chenfeng Zhang; Weili Gao; Yumei Guo; Lijie Zhang (Frontiers in Immunology)
BackgroundThe Mycobacterium abscessus complex (MABC), a multidrug-resistant environmental mycobacterium, rarely causes joint infections, which typically involve prosthetic joints. We describe the first case of native-knee M. abscessus infection linked to herbal steam therapy and osteoarthritis—a previously unreported scenario, accompanied by a literature review of 20 global MABC joint infection cases (2013–2024). Our findings present an alternative approach to the therapeutic guidelines for nontuberculous mycobacteria (NTM) infections, demonstrating successful clinical resolution in this single case using a short-course oral regimen.Case ReportA 54-year-old immunocompetent male with chronic knee osteoarthritis and a 6-year history of knee pain developed acute septic arthritis after knee-level high-temperature herbal steam baths. M. abscessus subsp. abscessus was identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and hsp65 gene sequencing. Despite premature discontinuation of therapy, a 3-month oral regimen of clarithromycin (1,000 mg/day) combined with linezolid (600 mg/day) achieved full functional recovery, evidenced by a daily walking capacity of 8,000 steps.ConclusionReview of 20 MABC joint infection cases from the literature revealed the knee as the most frequently affected site (55%), with the majority of patients (95%) having a history of joint surgery. This case highlights: 1) Herbal steam therapy, degenerative joint disease, and prior interventions as underrecognized risk factors; 2) Rapid molecular diagnostics (MALDI-TOF MS/hsp65) critical for early diagnosis; 3) Short-course oral therapy (clarithromycin/linezolid) as a potential option for localized infection when prolonged therapy is impractical.